China's and Italy's participation in peacekeeping operations : existing models, emerging challenges - De Guttry, Andrea; Sommario, Emanuele, 1975-; Zhu, Lijiang (Lexington Books, 2014)
China's and Italy's Participation in Peacekeeping Operations: Existing Models, Emerging Challenges examines the peacemaking efforts of these two countries through the lenses of international relations, history, sociology, and law. Using the specific experiences of Italy and China, this book addresses larger questions of how and why foreign powers intervene in the name of peace.